Comparative studies of student performance in physics and in other science subjects over a six year period - Wharton, Alwyn E. (Department of Physics, UWI, 1984)
This paper analyses examination marks of students in the Faculty of Natural Sciences, The University of the West Indies (UWI), St. Augustine during the period 1978-1983, to determine the magnitudes of systemic differences between courses in the first year and in the final year of the B.Sc. general degree programme. Most subjects are found to be reasonably close to faculty norm, but Year 1 mathematics is 7 marks too low and Year 1 computer science 13 marks too high. In an extreme case, a teacher could account for a deviation from the norm of 15 marks. Computer adjustment of marks is not recommended
Keywords: Faculty of Natural Sciences, UWI, St. Augustine